Clonotypic B cells in the peripheral blood of patients with multiple myeloma - Cremer, Friedrich Walter; Goldschmidt, Hartmut; Moos, Marion (Blood, 2001)
The frequency and the biologic significance of circulating clonal cells expressing CD19 in patients with multiple myeloma (MM) remain an issue of controversy. So far, in a small number of patients, the proportion of circulating clonotypic cells has been determined using different methods based on IgH-specific primers, and highly divergent results were reported.12Recently, a brief report from Rasmussen et al also addressed this question.3 In this paper, the numbers of clonal cells in the peripheral blood (PB) from patients with MM were investigated by quantitative real-time polymerase chain reaction (PCR). The levels of CD19+ cells in PB were assessed by flow cytometry, and the CD19 mRNA was quantitated by real-time RT-PCR.